2016
DOI: 10.1371/journal.pone.0160681
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Functional Expression of a Δ9- Fatty Acid Desaturase from an Antarctic Pseudomonas sp. A3

Abstract: Fatty acid desaturase enzymes play an essential role in the synthesis of unsaturated fatty acids. Pseudomonas sp. A3 was found to produce a large amount of palmitoleic and oleic acids after incubation at low temperatures. Using polymerase Chain Reaction (PCR), a novel Δ9- fatty acid desaturase gene was isolated, cloned, and successfully expressed in Escherichia coli. The gene was designated as PA3FAD9 and has an open reading frame of 1,185 bp which codes for 394 amino acids with a predicted molecular weight of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…A3 and cold‐tolerant Pseudomonas sp. A8, the genes PA3FAD9 and PA8FAD9 coding, respectively, for a membrane Δ9‐FA desaturase protein . Similar to detected in our study with the expression of desA of P. putida A (ATCC 12633), the functional expression of the genes PA3FAD9 and PA8FAD9 in E. coli transetta (DE3) displayed a significant increase in the proportions of palmitoleic acid content in recombinant E. coli cells, confirmimg an active Δ9‐FA protein.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…A3 and cold‐tolerant Pseudomonas sp. A8, the genes PA3FAD9 and PA8FAD9 coding, respectively, for a membrane Δ9‐FA desaturase protein . Similar to detected in our study with the expression of desA of P. putida A (ATCC 12633), the functional expression of the genes PA3FAD9 and PA8FAD9 in E. coli transetta (DE3) displayed a significant increase in the proportions of palmitoleic acid content in recombinant E. coli cells, confirmimg an active Δ9‐FA protein.…”
Section: Discussionsupporting
confidence: 87%
“…) that are conserved in most membrane desaturases and that have been shown to be important for catalysis and presumed to compose the Fe‐binding active centers of these enzymes . The Kyte‐Doolittle hydropathy profiles of DesA revealed two hydrophobic regions (between amino acids 10–33 and 137–160) similar to the sequence profiles of known membrane‐associated desaturases . Although this study does not advance on the purification of this enzyme, the characteristics observed in the predicted DesA protein (histidine boxes and hydrophobic domains) are consistent with the topological models derived from studies performed with other desaturases, such as yeast A9 acyl‐CoA desaturase , mouse steaoryl‐CoA desaturase , and acyl lipid Δ5 desaturase from Bacillus subtilis .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Pseudomonas sp. AMS8 ∆9-fatty acid desaturase and sequences from several other ∆9-fatty acid desaturases has revealed the three conserved-histidine boxes common to all membranebound desaturases in bacteria (Garba et al, 2016b;Li et al, 2009), fungi (Chen et al, 2013) and animals (Bai et al, 2015) (Figure 1). The human integral membrane stearoyl-CoA desaturase (PDB ID: 4ZYO) and mouse stearoyl-coA desaturase (PDB ID: 4YMK) have been solved to a resolution of 3.25 Å and 2.6 Å, respectively.…”
Section: Sequence Of the ∆9-fatty Acid Desaturase Protein And Templatmentioning
confidence: 99%